Gastrointestinal helminthiases of dogs with molecular genetic identification of echinococcosis - Abdybekova , A.; Yalysheva , S.; Zhaksylykova , A.; Uakhit, R.; Kiyan, V. (Eurasian Journal of Applied Biotechnology, 2022)
Echinococcosis is a serious zoonotic disease caused by a larval stage of the tapeworm from genus Echinococcus. Dogs act as definitive hosts and infect humans and farm animals. The article presents the results of a study of feces of 1020 dogs from Zhambyl, Kyzylorda, Turkestan, Almaty, Zhetysu, Karaganda, Aktobe, Pavlodar and Akmola regions for Echinococcus granulosus, collected in 2021-2022. Eggs of Taeniia spp., Toxocara canis, Toxascaris leonina, Trichuris vulpis, Ancylostoma caninum were found using copro-ovoscopy methods. Helminth samples were differentiated by amplification and sequencing using the Ef1a translation elongation factor marker gene. Based on the analysis of the nucleotide sequences of 22 egg samples, two samples were identified as E. granulosus. Based on the G protein primer, the G1 genotype was established. These samples were deposited in the NCBI GenBank database (accession numbers ON630760 and ON630761). For the first time, molecular genetic characterization of the echinococcosis causative agent in the final hosts was carried out in Kazakhstan.